(untitled) (Experimental biology, 2021)
In this review multi-omics (transcriptomic and proteomic) research approaches that have been widely implemented in modern microbiology are examined. The transcriptomic approach is important for predicting the resistance of microorganisms to specific antibiotics, as well as for understanding the mechanisms of the emergence of antibiotic resistance. In this review, the issues of studying the transcriptional response in microorganisms after in vitro exposure to subinhibitory concentrations of antimicrobial drugs are most extensively examined. It has been shown that antibiotics induce both phenotypic and genetic changes in bacterial cells, contributing to the emergence of resistance to them. Likewise, a proteomics-based approach broadens understanding of the bacterial strategy for antibiotic resistance, as well as improved understanding of the mechanisms by which antimicrobial resistance emerges, which will facilitate controlling of the growing epidemic of antibiotic-resistant infections in the future. In this review, the advantages of using one of the proteomics approaches widely used in clinical microbiology, MALDI-TOF MS, are considered more extensively. It has been shown that this approach is a more powerful tool for studying the protein profile in comparison with other methods. Thus, the development of high-throughput transcriptomic and proteomic methods made analysis of large datasets of mRNA and proteins possible, which allows identifying functionally significant networks of intermolecular interactions, and thereby allowed to expand the modern understanding of mechanisms underlying the emergence of resistance to antimicrobial drugs.